2020
DOI: 10.1111/jrh.12476
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Disparities in Coronavirus Incidence and Mortality in the United States: An Ecological Analysis as of May 2020

Abstract: Purpose: This ecological analysis investigates the spatial patterns of the COVID-19 epidemic in the United States in relation to socioeconomic variables that characterize US counties.Methods: Data on confirmed cases and deaths from COVID-19 for 2,814 US counties were obtained from Johns Hopkins University. We used Geographic Information Systems (GIS) to map the spatial aspects of this pandemic and investigate the disparities between metropolitan and nonmetropolitan communities. Multiple regression models were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
207
2
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(236 citation statements)
references
References 35 publications
12
207
2
5
Order By: Relevance
“…Second, as long as different models are required to tell different stories (34 estimations in this case), a significant part of the municipal variation in infections and deaths can be explained by a rather small number of variables (as inTable 5). In any case, all the results highlight the role of social determinants of health in explaining the dissimilar impact of COVID-19 in the MR as well as other findings in other countries about unequal distribution of COVID-19(83)(84)(85)(86).…”
supporting
confidence: 71%
“…Second, as long as different models are required to tell different stories (34 estimations in this case), a significant part of the municipal variation in infections and deaths can be explained by a rather small number of variables (as inTable 5). In any case, all the results highlight the role of social determinants of health in explaining the dissimilar impact of COVID-19 in the MR as well as other findings in other countries about unequal distribution of COVID-19(83)(84)(85)(86).…”
supporting
confidence: 71%
“…Using state-level data ignores population heterogeneity that could obscure the effects of COVID-19 on marriage. Specifically, cases and fatalities in the early COVID-19 experience have been primarily located in large urban areas (Zhang and Schwartz 2020). To focus on marriage in such a setting, we explore marriage data in the Dallas-Fort Worth-Arlington, Texas (DFW) Metropolitan Statistical Area (MSA).…”
Section: Datamentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the viral agent of Coronavirus Disease 2019 (COVID- 19). Currently a global pandemic, it was first identified in Wuhan city, Hubei province, China and has since spread worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…These vulnerabilities, combined with healthcare infrastructure shortfalls, make rural areas potentially high mortality areas [18]. A spatial study found hotspots in COVID-19 incidence and mortality rates per 100,000 in both urban and rural areas [19]. Another study found higher mortality rates per capita in rural, vulnerable counties compared to diverse, urban counties [20].…”
Section: Introductionmentioning
confidence: 99%